INCIDENTES OCASIONADOS POR NEGLIGENCIA DEL AGENTE CIVIL DE TRÁNSITO AL EMITIR UNA CITACIÓN POR INFRACCIONES DE TRÁNSITO COMETIDAS EN EL ECUADOR - Coronel Aillón, Darwin Vicente (2016)
Ecuadorian law and legal science technology advances in an extraordinary way in different legal areas, which is leaving some loopholes in the various bodies of law, the same should be taken into consideration to be modified in order to ensure good living of all those who make up the Ecuadorian state, as in the case of the first of the Organic Law on Land Traffic and Road Transport Safety section, in which civilians traffic police referred to, considering them as servers public, specialized in vehicle system, and cutlery competition to direct and control traffic within our territory, but not found a provision is a sanction to these officials which are held negligent in the performance of their duties, because with impose a sanction perform their work is guaranteed with these antecedes this thesis entitled: "INCIDENTS OCCASIONED NEGLIGENCE AGENT TO CIVIL TRAFFIC ISSUE A SUMMONS FOR TRAFFIC VIOLATIONS COMMITTED IN ECUADOR", is intended to give legal criteria given, to punish misconduct in the performance of the tasks entrusted to civilian traffic officer, so that in the end avoid their bad actions within their functions, and thus prevent further hurting the state and society for its misconduct within its functions, thus ensuring good living of all those who make up the Ecuadorian nation, for which it took into account the different criteria issued by judicial officials and the general public through field research. 5 The methodology used to develop this research was to conduct surveys and interviews to different administrators of justice the same that could not punish the offender by the lack of regulations in the respective ballot summons for a traffic violation and public at large, who have been victims of sanctions without proper foundation, enabling find coherent alternative of adding a clause to Article 30.1 of the first section of the Organic Law of Transportation road traffic and road safety. Implementing a clause to the first of the Organic Law on Land Transportation, Traffic and Road Safety Section was to locate certain sanctions to civil traffic cop they hold negligent in performing their daily work, the same that would ensure proper application the rules on the ballot citation, which allow the administration of justice act properly punishing the offender and impose the appropriate penalty, which will benefit the state and society since these resources can invest in the development of new projects that will for the benefit of the community in general.